Analysis of Performance and Security in Modern Computer Networks - Satria, Welnof (Universitas Dharmawangsa Medan, 2024)
Computer networks have become the cornerstone of communication and data transfer in today's digital era. This article provides an in-depth examination of various critical aspects of computer networks, including network architecture, protocols, hardware, and the issues surrounding security and performance. Emphasizing the significance of robust network design, the study evaluates different topologies, such as star, bus, ring, and mesh, and their impact on network efficiency and reliability. Furthermore, it explores essential network protocols like TCP/IP, UDP, and HTTP/HTTPS, highlighting their roles in ensuring efficient and reliable data communication. The analysis extends to modern hardware components, such as routers, switches, and security devices like firewalls and IDS/IPS, which are integral to network management. Additionally, the article delves into the latest networking technologies, including 5G, the Internet of Things (IoT), and cloud computing, discussing their transformative potential and the associated challenges in their deployment and management. This comprehensive overview aims to provide valuable insights for practitioners and researchers in developing innovative and effective solutions for secure and high-performance networks.